1998
DOI: 10.1099/00221287-144-7-1815
|View full text |Cite
|
Sign up to set email alerts
|

SepA, the 110 kDa protein secreted by Shigella flexneri: two-domain structure and proteolytic activity

Abstract: Shigellosis is characterized by a strong inflammatory response which is induced by bacteria invading the colonic mucosa. Characterization of a sepA mutant indicated that SepA, the major protein secreted by Shigeh flexneri growing in laboratory media, might be involved in invasion and destruction of the host intestinal epithelium. The sequence of the first 500 residues of mature SepA (110 kDa) is homologous to that of the N-terminal region of l g A l proteases. To investigate the potential proteolytic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 36 publications
2
40
0
2
Order By: Relevance
“…It is also possible that the many serotypes are adapted to different variants of the general niche occupied, and that the selection relates to competition between different Shigella clones which differ in details of their adaptation to the niche. The observation that senA (29), a toxin gene apparently under selection pressure for change, and sepA, known to play a role in virulence in S. flexneri serotype 2a (3,4), are absent in some Shigella strains supports the hypothesis that Shigella strains differ in the details of their adaptation to their mode of pathogenesis. A similar explanation may account for the observation that genes under selection pressure differ between E. coli and S. enterica.…”
Section: Resultsmentioning
confidence: 54%
“…It is also possible that the many serotypes are adapted to different variants of the general niche occupied, and that the selection relates to competition between different Shigella clones which differ in details of their adaptation to the niche. The observation that senA (29), a toxin gene apparently under selection pressure for change, and sepA, known to play a role in virulence in S. flexneri serotype 2a (3,4), are absent in some Shigella strains supports the hypothesis that Shigella strains differ in the details of their adaptation to their mode of pathogenesis. A similar explanation may account for the observation that genes under selection pressure differ between E. coli and S. enterica.…”
Section: Resultsmentioning
confidence: 54%
“…It has been shown that the serine protease motif is important for phenotypic functions such as cytotoxic and proteolytic activities (20). Some authors predict that casein hydrolytic activity is dependent on the conserved serine protease active-site motif (2,3). The difference in this motif may be the reason that Vat was negative in tests for proteolytic activity on casein-based substrate (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…In 1995, Benjelloun-Touimi et al described a Tsh homologue designated SepA (for Shigella extracellular protein), which is the major extracellular protein of S. flexneri (22). Investigation of the proteolytic activity of SepA utilizing a wide range of synthetic peptides found that SepA hydrolyzed several of these substrates and that the activity was inhibited by the serine protease inhibitor phenylmethylsulfonyl fluoride (PMSF) (23). Several SepA-hydrolyzed peptides were described as specific substrates for cathepsin G, a serine protease produced by polymorphonuclear leukocytes that was proposed to play a role in inflammation.…”
Section: Serine Protease Autotransporters Of the Enterobacteriaceaementioning
confidence: 99%